Prvi seznam makromicet s širšega območja Šaleške doline - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2003)
The inventory of macrofungi in the Šalek Valley was made in 2001 and 2002. In total, 316 species of higher fungi were determined. Among them, the following fourteen species are protected by law in Slovenia: Amanita caesarea, Amanita strobiliformis, Boletinus cavipes, Boletus regius, Cantharellus cibarius var. amethysteus, Craterelus lutescens, Chroogomphus helveticus, Gomphus clavatus, Gomphidius roseus, Gyroporus cyanescens, Phaeolepiota aurea, Sparassis brevipes, Strobilomyces strobilaceus and Tricholoma colossus. In addition, several rare species were found in the Šalek Valley. Due to the high species richness, the inventory of macrofungi in the Šalek Valley should be continued in the future. The list was made from the bioindicative point of view and is, moreover, compared with legal documents regarding the endangered European macrofungi.
Keywords: biotska pestrost; glive; seznami; Šaleška dolina